2015
DOI: 10.1016/j.jagp.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Social Support from Church and Family Members and Depressive Symptoms Among Older African Americans

Abstract: Objectives This study examined the influence of church and family based social support on depressive symptoms and serious psychological distress among older African Americans. Methods The analysis is based on the National Survey of American Life (NSAL). Church and family based informal social support correlates of depressive symptoms (CES-D) and serious psychological distress (K6) were examined. Data from 686 African Americans aged 55 years or older who attend religious services at least a few times a year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
119
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 42 publications
13
119
0
Order By: Relevance
“…Further, PTSD is also commonly associated with learning and memory impairments (Burriss et al, 2008) and is comorbid with major depressive disorder (Amaya-Jackson et al, 1999) and substance abuse (Buckley, Mozley, Bedard, Dewulf, & Greif, 2004; Thomas et al, 2010)—all of which have consequences for social functioning and personal relationships. Social relationships may be particularly important in understanding African Americans’ mental health, (Chatters, Taylor, Woodward, & Nicklett, 2015; Lincoln, 2000; Taylor, Chae, Lincoln, & Chatters, 2015)as prior research has found that positive relationship qualities, such as social support and subjective closeness, are predictive of more favorable mental health outcomes, and negative relationship qualities, such as negative interactions, are predictive of poorer mental health outcomes (Lincoln, 2000; Nguyen, Chatters, Taylor, & Mouzon, 2015; Taylor et al, 2015). The purpose of this study is to investigate the relationship between social support, negative interactions and 12-month PTSD in a nationally representative sample of African Americans in the U.S.…”
mentioning
confidence: 99%
“…Further, PTSD is also commonly associated with learning and memory impairments (Burriss et al, 2008) and is comorbid with major depressive disorder (Amaya-Jackson et al, 1999) and substance abuse (Buckley, Mozley, Bedard, Dewulf, & Greif, 2004; Thomas et al, 2010)—all of which have consequences for social functioning and personal relationships. Social relationships may be particularly important in understanding African Americans’ mental health, (Chatters, Taylor, Woodward, & Nicklett, 2015; Lincoln, 2000; Taylor, Chae, Lincoln, & Chatters, 2015)as prior research has found that positive relationship qualities, such as social support and subjective closeness, are predictive of more favorable mental health outcomes, and negative relationship qualities, such as negative interactions, are predictive of poorer mental health outcomes (Lincoln, 2000; Nguyen, Chatters, Taylor, & Mouzon, 2015; Taylor et al, 2015). The purpose of this study is to investigate the relationship between social support, negative interactions and 12-month PTSD in a nationally representative sample of African Americans in the U.S.…”
mentioning
confidence: 99%
“…Rural low-income mothers of children 12 years old or younger (44% minority) who reported higher levels of attendance at religious services also reported lower level of depressive symptoms (Garrison, Marks, Lawrence, & Braun, 2004). However, other researchers have not found a relationship between attendance at religious services and depressive symptoms in men and women (Chatters et al, 2014; Krause, Bruce, Hayward, & Woolever, 2014). …”
Section: Depression and Church Attendancementioning
confidence: 82%
“…Older adults from Australia who consistently attended religious services reported lower levels of depressive symptoms compared with older adults who did not attend religious services (Law & Sbarra, 2009). Similarly, older African Americans who attended religious services nearly every day had less psychological distress (Chatters, Taylor, Woodward, & Nicklett, 2014). Rural low-income mothers of children 12 years old or younger (44% minority) who reported higher levels of attendance at religious services also reported lower level of depressive symptoms (Garrison, Marks, Lawrence, & Braun, 2004).…”
Section: Depression and Church Attendancementioning
confidence: 99%
See 1 more Smart Citation
“…1 Given the high rate of religious service attendance and the central role of church-based social supports in many African American communities, 1 Chatters et al 3 examined the influences of church and family informal support networks on depressive symptoms among older African Americans. Crosssectional data were included from 686 African Americans (age 55 years or older) who endorsed attending religious services in the National Survey of American Life.…”
mentioning
confidence: 99%